Experience Feedback from Swedish In- Situ Thermal Treatment Projects - A retrospective study based on documents and interviews from five sites - Johnsson, Olle (My University, 2022)
Ever since the late 90’s, when Sweden adopted a series of environmental quality objectives, the challenge of remediating contaminated soils has been an on going task. Parallel to the growth of the knowledge base on the national situation, new technologies have emerged with unique features and abilities. This thesis focus on one of the technologies that has gained lots of traction due to it’s ability to decontaminate chlorinated solvents in areas difficult to access: In-Situ Thermal Treatment (ISTT). To this date, ISTT has been deployed nationally over a hand-full of times: projects that now are constituents of an increasing knowledge-base on the Swedish application. The aim of this thesis is to review In-Situ Thermal Treatment-projects conducted in Sweden and compile experiences in order to provide feedback on the application. The study was conducted by three tasks: 1) identification of relevant projects 2) a document study on publications related to the targeted projects, and 3) a set of interviews with actors involved in ISTT-project organisations. The results were processed with main focus on cross-project comparability and international experience. Findings include the Swedish performance being well in line with, in terms of remediation results, claims in literature and international experience. However, the effort and expenses to attain project goals is subject to considerable variation. A weak trend was identified between financial performance, efforts put in to preparatory work and perceived project success (expressed in interviews). Projects that put more efforts into characterizing the contamination showed better financial results as well as a more unified view of the project performance. An additional feature that was recurrently voiced in the interviews was the need for a large information flow within the projects. The reason is that ISTT-projects require large preparatory efforts of measurements, sampling, and data collection in order to create an accurate site characterization and enable good, information-based decisions. Further, the ISTT technology provides the possibility of extensive progress monitoring. The opinions on the size of the required information flow varies. Technically involved actors generally lifts the process monitoring and control as a security and strength of ISTT and emphasizes an accurate demarcation of the treatment area as crucial factor for a cost efficient remediation. On the other end, actors operating more distant from the technology and on-site action (i.e. stakeholders such as municipalityand environmental protection agency representatives) may experience an information asymmetry. Multiple of these representatives expressed that they struggled to process and evaluate the progress of the treatment and had to completely rely on procured contractor and/or advisor.
Keywords: soil remediation; experience feedback; decontamination; ISTT; TCH; ERH; In-Situ